Graphene oxide induced dynamic changes of autophagy-lysosome pathway and cell apoptosis via TFEB dysregulation in F98 cells - Danni Dai; Yuming Chen; Qiuyu Wang; Chunlin Wang; Chao Zhang (Ecotoxicology and Environmental Safety, 2022)
The extensive application of graphene oxide (GO) nanomaterials increases the risk of their release into the environment, thus posing a threat to the human body. Multiple studies indicate that GO could lead to neurotoxicity, while the intricate biological effects of GO in astrocytes remain unclear. The autophagic disorder was considered an important part of the exposure risk of GO in the application of neuromedicine. This study explored the key regulators mediating the autophagic process in rat astroglioma-derived F98 cells caused by GO, especially the dynamic changes in the cellular physiological state over time. We identified transcription factor EB (TFEB), a critical regulator of the autophagy-lysosome pathway (ALP), as a crucial factor in GO-induced autophagy flux blockade and cell apoptosis. Specifically, the prolonged exposure to GO increased the amount of its cellular internalization, which gradually prevented TFEB from entering the nucleus, thereby leading to the subsequent ALP dysfunction and excessive cell apoptosis. Furthermore, STIP1 homology and U-Box containing protein 1 (STUB1), an E3 ubiquitin ligase, was responsible for GO-triggered TFEB dysregulation, and overexpression of STUB1 helped alleviate GO cytotoxicity. Our study highlights that impaired TFEB activity underlies compromised autophagy flux in GO-induced apoptosis and opens up new avenues for the application of GO-based nanotherapeutics with specific autophagy-regulating properties in the central nervous system.